The Relationship Between Self-Concept and Psychological Welfare on Influencers in social media - Mutia Mawardah; Bella Wirahma (Budapest International Research and Critics University, 2022)
With the advent of the 4.0 era, the lifestyle and needs of internet users are increasing, and daily activities are all carried out using the internet network. Internet stands for Interconnected Network and is defined as a very wide or worldwide computer network. This study aims to determine the relationship between self-concept and psychological well-being on social media influencers. The method used by researchers here is a quantitative method using a scale. Based on the results of research on the factors that influence influencers on social media, it shows that they have a low self-concept because it is difficult to accept the present. This situation causes more and more new influencers who have the desire to always look different on social media. Acting to provide content that people know about.